Formulation and Physical Evaluation of Papaya Leaf (Carica papaya L.) Ethyl Acetate Fraction Cream Preparation as Anti Acne Against Propionibacterium acne Bacteria - Farda, Zais; Rahayu, Titi Pudji; Kiromah, Naelaz Zukhruf Wakhidatul (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Acne or acne vulgaris is a disease in the form of inflammation of multiple sebaceous glands caused by the bacteria Propionibacterium acne. Papaya leaves are a plant that can potentially be used as an acne treatment. To determine the antiacne activity of papaya leaf ethyl acetate fraction cream preparations caused by Propionibacterium acne bacteria. The ethyl acetate fraction of papaya leaves are made into a cream preparation with varying concentrations of ten, fifteen, and twenty percent. The results of the cream preparation test met the physical property standards. Still, the viscosity in formulation three did not meet the standards, and formulas two and three did not meet the cream stability test standards. Antibacterial tests show that all formulas have inhibitory power against bacteria. The average inhibition zone results in formula one, formula two, and formula three were 4.99 ± 0.48 mm, 6.85 ± 0.48 mm and 10.12 ± 1.42 mm. Formula One papaya leaf fraction cream fulfills all the physical characteristics of the preparation. All papaya leaf ethyl acetate fraction cream preparations are antibacterial against Propionibacterium acne. So, research can be developed using the ethyl acetate fraction of papaya leaves in various preparations, and activity tests against other bacteria can be carried out.